Evaluating the Impact of Alternative Material-Based Catalytic Converters on Automotive Exhaust Emissions - Ariyanto, Sudirman Rizki; Warju, Warju; Arifianti, Lailatus Sa'diyah Yuniar; Komarudin, Komarudin; Nugraha, Ata Syifa' (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2025)
Pollution air in cities in Indonesia, such as Jakarta, Tangerang, and Bandung, is especially caused by exhaust emissions from vehicle motorized, like carbon monoxide (CO) and hydrocarbons (HC), which originate from burning material burn the ones that don't perfect. Technological catalytic converters are used to reduce emissions, but converters made from metal have their own cost. This study evaluates exhaust Metallic Catalytic Converter (MCC) technology with alternative materials copper (Cu). The result shows that the MCC Cu exhaust system is significantly more effective in reducing CO and HC emissions compared with exhaust without the original equipment manufacturer (OEM) catalyst and exhaust. The average CO emissions are 2.13 %Vol and HC emissions are 198 ppmVol, lower compared to the second type of exhaust. Findings This shows that MCC Cu exhaust is not only more effective in reducing danger but is also more economical compared to catalytic converters made from metal noble, offering a solution sustainable and affordable for problem pollution air from vehicles.